Yellow Wine Polyphenolic Compound Protects Against Doxorubicin-Induced Cardiotoxicity by Modulating the Composition and Metabolic Function of the Gut Microbiota. (30th September 2021) - Lin, Hui; Meng, Liping; Sun, Zhenzhu; Sun, Shiming; Huang, Xingxiao; Lin, Na; Zhang, Jie; Lu, Wenqiang; Yang, Qi; Chi, Jufang; Guo, Hangyuan
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Dietary polyphenols help to prevent cardiovascular diseases, and interactions between polyphenols and gut microbiota are known to exist. In this study, we speculated that gut microbiota-mediated metabolite regulation might contribute to the anticardiotoxic effects of yellow wine polyphenolic compound (YWPC) in doxorubicin (DOX)-treated rats. Methods: 16S-rDNA sequencing was performed to analyze the effects of YWPC on the gut microbiota in DOX-treated rats (n=6). Antibiotics were used to investigate the contribution of the altered microbiome to the role of YWPC (n=6). Plasma metabolomics were also analyzed by untargeted gas chromatography-mass spectrometry systems. Results: YWPC ameliorated DOX-mediated cardiotoxicity, as evidenced by increased cardiac and mitochondrial function and reduced levels of inflammation and myocardial apoptosis ( P <0.05 for all). The low abundance of Escherichia – Shigella, Dubosiella, and Allobaculum, along with enrichment of Muribaculaceae_unclassified, Ralstonia, and Rikenellaceae_RC9_gut_group in the gut, suggested that YWPC ameliorated DOX-induced microbial dysbiosis. YWPC also influenced the levels of metabolites altered by DOX, resulting in lower arachidonic acid and linoleic acid metabolism and higher tryptophan metabolite levels ( P <0.05 for all). Correlational studies indicated that YWPC alleviated DOX-induced inflammation and mitochondrial dysfunction by modulating the gut microbial community and its associated metabolites. Antibiotic treatment exacerbated cardiotoxicity in DOX-treated rats, and its effect on the gut microbiota partly abolished the anticardiotoxic effects of YWPC, suggesting that the microbiota is required for the cardioprotective role of YWPC. Conclusions: YWPC protected against DOX-induced cardiotoxicity in a gut microbiota–dependent manner. This supports the use of dietary polyphenols as a therapeutic approach for the treatment of cardiovascular diseases via microbiota regulation.